Effectiveness of Cryogen Tetrfluoroethane on Elimination of Gingival Epithelium and its Clinical Application in Gingival Depigmentation–Histological Findings and Case Series - Kumar, Santhosh (JCDR Research and Publications (P) Limited, 2013)
Objective: To histologically assess and clinically co-relate the effectiveness of cryogen Tetrafluoroethane (TFE) for gingival depigmentation procedure. Material and Methods: Twelve patients having unaesthetic gingival melanin pigmentation were included in the study. Gingival tissues of eight patients having gingival melanin pigmentation undergoing gingivoplasty or gingivectomy for crownlengthening were exposed to the cryogen and this was used for the histological examination. Gingivectomies were done after 8, 24, 96 hours and after a week of application of tetrafluoroethane. Four fair skinned patients complaining of unaesthetic gingival hyperpigmentation underwent gingival depigmentation using Tetrafluoroethane cryogen. Results: Histologically after 96 hours of application of cryogen there was complete loss of retepegs and epithelial detachment from the corium was evident. Complete re – epithelialisation was noted after a week and was clinically correlated. Conclusion: We therefore, concluded that histologically tetrafluoroethane can effectively destroy gingival epithelium without causing damage to the connective tissue and clinically the color of the gingiva had more pleasing appearance 6 months postoperatively. Hence the cryogen can be used safely for depigmentation procedure.